Pengaruh Profitability, Liquidity, Leverage, Dividend Policy, Firm Size, dan Firm Growth terhadap Nilai Perusahaan - Auliya Kusuma Wardani Mahardikari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Firm value is the company's goal is maximizing the present value of all future shareholder profits. Observe the effect of profitability, liquidity, leverage, dividend policy, firm size, and firm growth towards the firm value of various industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 are the aim of this research. This type of research is explanative with a quantitative approach. Price Book Value (PBV) in this research used to measure the firm value. The Sampling data used in this research is purposive sampling techniques and consisted of 12 companies of 51 companies as a population. Analysis techniques use multiple linear regression. This research gets the result that profitability, liquidity, and dividend policy have a positive significant, firm size and firm growth does not affect firm value, and then leverage has a significant negative effect on firm value.